2017
DOI: 10.1016/j.tem.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role for Mammalian Target of Rapamycin in Male Fertility

Abstract: Male fertility is modulated by environmental, endocrine, paracrine, and metabolic cues. Mammalian target of rapamycin (mTOR) coordinates many cellular events in response to those signals. Here, we discuss how the mTOR pathway integrates and mediates signals throughout the male reproductive system, acting as a central player in the control of spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…According to a recent study that supports our results, increased activity of mTORC1 due to decreased liver kinase B1 leads to an increase in Sertoli cell (SC) proliferation, with notable deficiencies in SC polarity and localisation of junctional complexes in young mice (Oliveira et al, ). Moreover, our findings were supported by the hypothesis of Hobbs et al, who stated that a subset of spermatogonia may vary in their response to increased mTORC1 and may lead to impaired spermatogenesis (Hobbs et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to a recent study that supports our results, increased activity of mTORC1 due to decreased liver kinase B1 leads to an increase in Sertoli cell (SC) proliferation, with notable deficiencies in SC polarity and localisation of junctional complexes in young mice (Oliveira et al, ). Moreover, our findings were supported by the hypothesis of Hobbs et al, who stated that a subset of spermatogonia may vary in their response to increased mTORC1 and may lead to impaired spermatogenesis (Hobbs et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…This finding suggests that mTORC1 has a role in spermatogenesis. Moreover, both mTOR complexes are involved in the regulation of blood testicular barrier dynamics during spermatogenesis (Oliveira, Cheng, & Alves, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in other cellular systems, such as intestinal epithelial cells (Fazolini et al 2015), leptin activates the mTOR pathway triggering lipid droplet formation. mTOR controls Sertoli cells redox balance and metabolism (Jesus et al 2016) and has been discussed as a central rheostat regulator of male reproductive potential (Jesus et al 2017, Oliveira et al 2017. Thus, it may be a key player in obesity-induced male subfertility/infertility by controlling lipid droplet formation in testicular cells, among other mechanisms.…”
Section: Energy Balance Hormonal Dysfunction and Male Reproductionmentioning
confidence: 99%
“…These metabolic processes depend on signalling pathways network. The mammalian target of rapamycin (mTOR) kinase emerged as pivotal for these processes (for review Oliveira et al, 2017), controlling mitochondrial bioenergetics and glucose metabolism. GLP-1 interferes with mTOR pathway (Park et al, 2015) and recently it was suggested that mTOR has an essential role in male reproduction (Jesus et al, 2017).…”
Section: Introductionmentioning
confidence: 99%